(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
Living with technology and producing enormous amount of data is a common thing now. As digitization has become a vital part of routine life, data collection has resulted in the accumulation of huge amounts of data that can be used in various valuable application domains. Effective investigation and utilization of big data is a key factor for success in many business and service domains, including the smart city domain. This paper reviews the applications of big data to support smart cities. It further explores the future of the smart city and big data and acquaints us about challenges and benefits of incorporating big data applications for smart cities.